(untitled) (Nepalese Journal of Management Research, 2025)
This study looks at the opinions of investors in Chitwan, Nepal, about mutual funds as well as their general investing habits, risk tolerance, and decision-making variables. The study identifies drivers like yield, risk, liquidity, and security as crucial elements that impact investors’ choices, based on a sample of 101 respondents from a range of socioeconomic backgrounds. It was shown that although most investors recognize the advantages of mutual funds, they still rely on brokers, suggesting that mutual fund accessibility and education might be improved. In addition, the respondents frequently mentioned issues like exorbitant prices, service delivery time, and branch distance, all of which could lower investor satisfaction and restrict the pool of potential investors. Mutual funds, particularly closed-ended ones, are drawing more comparatively younger and moderately earning investors, according to the report. Additionally, it was determined that digital sources, such as the internet, were the most efficient among all of the information sources. The Chitwan region may see a rise in mutual fund investors, according to this report, which is why businesses should focus on improving outreach and fixing service issues. These steps have the potential to boost investor confidence and have a big influence on the region’s access to financial inclusion and wider economic scenarios.